The safety of renal denervation as assessed by optical coherence tomography: pre- and post-procedure comparison with multi-electrode ablation catheter in animal experiment - Wenzheng Han (Hellenic Journal of Cardiology, 2020)
Objective: To prove the effectiveness and safety of multi-electrode ablation catheter in renal denervation (RDN) by optical coherence tomography (OCT). Methods: Sixteen renal arteries were enrolled from 8 pigs. Angiography and OCT were performed to analyze the morphological changes before RDN and at 1-month follow-up. Blood pressure and creatinine were measured to prove the effectiveness and safety of the catheter. Results: One renal artery was excluded because of the small diameter. Fifteen renal arteries successfully underwent renal denervation and OCT. Mean blood pressure was significantly reduced at 1 month after RDN (122.40 ± 3.54 mmHg vs. 106.50 ± 2.06 mmHg, n = 8, P < .001). Creatinine follow-up after 1 month showed no significant change (45.37 ± 7.44 vs. 65.87 ± 49.20 μmol/L, n = 8, P = 0.275). The minimal lumen diameter showed that the renal artery immediately narrowed after the procedure (7.17 ± 0.60 mm vs. 5.93 ± 0.97 mm, n = 15, P < .001). Vasospasm, vascular wall edemas, and thrombus formations all showed significant changes after the procedure except renal artery dissection (0% vs. 21.4%, P = 0.067) under the OCT. Adverse event as renal artery occluded showed no significant difference (0% vs. 6.7%, P > .05). OCT results showed no significant difference in vasospasm, dissections, wall edemas, and thrombus formations (P > .05) at 1 month after the procedure. Conclusion: This multi-electrode ablation catheter could cause minor injury to renal artery instantly after RDN, but it is found to be safe in the animal model at 1-month follow-up.